The Influence of Regional Language Leaflets about Stunting on Increasing the Knowledge of Mothers of Toddlers - Manik, Inggrit Rita Uli; Boseren, Selina (Indonesian Journal of Global Health Research, 2024)
Stunting is a serious health issue affecting children's growth and development, particularly in areas with limited access to nutritional and health information, such as Biak Regency in Papua Province. This study aims to measure the impact of regional language leaflets on increasing mothers’ knowledge of stunting. The use of local language is expected to strengthen mothers' understanding of the causes, impacts, and prevention of stunting, as well as to enhance the effectiveness of health communication at the community level. This quantitative pre-experimental study employed a one-group pretest-posttest design with 20 mothers from Samau Village, selected through total sampling. Data collection used a validated and reliable stunting knowledge questionnaire with a Cronbach's Alpha of 0.908. The results were analyzed using the Wilcoxon Signed-Rank Test. Findings indicated that most respondents were aged 20-35, had high school education, were housewives, and had multiple children. Before the intervention, 95% had limited knowledge about stunting, but after the intervention, 75% demonstrated good understanding. The Wilcoxon Signed-Rank Test yielded a p-value of 0.000, confirming the effectiveness of using local language leaflets to improve stunting awareness.